2017
DOI: 10.5455/msm.2017.29.172-175
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Responsiveness Level in Iranian Public and Private Physiotherapy Clinics: a Cross-Sectional Multi-center Study

Abstract: Introduction:Responsiveness is a main goal of health systems. Responsiveness focus on the non-medical aspects of health services delivery. This study was aimed to assess responsiveness level in public and private physiography clinics.Methods:In this multicenter cross sectional study, 403 patients refers to 16 public and 64 private physical therapy clinics were studied randomly in Ahvaz, Iran, from 2013 to 2014. Data were collected based on a valid health system responsiveness questionnaire that was developed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
(15 reference statements)
1
3
0
Order By: Relevance
“…This discrepancy could be due to different contexts as Wang studied in rural area where confidentiality may be more of concern in small population compared with large populations such as in Tehran. Results regarding the poorest performing domains supports those of Piroozi et al in Sanandaj, a western city of Iran in 2014–2015 ( 27 ) and Torabipour et al that investigated the responsiveness of physiotherapy clinics in Ahvaz in south of Iran in 2014 ( 39 ).…”
Section: Discussionsupporting
confidence: 79%
“…This discrepancy could be due to different contexts as Wang studied in rural area where confidentiality may be more of concern in small population compared with large populations such as in Tehran. Results regarding the poorest performing domains supports those of Piroozi et al in Sanandaj, a western city of Iran in 2014–2015 ( 27 ) and Torabipour et al that investigated the responsiveness of physiotherapy clinics in Ahvaz in south of Iran in 2014 ( 39 ).…”
Section: Discussionsupporting
confidence: 79%
“…For categorization 1, health system responsiveness is understood primarily as a performance and service quality indicator [ 53 , 62 ]. This seems to originate in the WHR2000 on health system performance and was likely also influenced by the increased importance given to ‘patient-centered care’ in that decade, which includes emphasis on non-clinical aspect of care.…”
Section: Resultsmentioning
confidence: 99%
“…Across items in this category, the WHO responsiveness tool has been validated and adaptations suggested – such as the addition of domains for education and information sharing [ 3 , 36 ], effective care [ 73 , 74 ], trust [ 73 , 75 ], coordination and responsibility [ 62 ]. Several authors have argued that the WHO’s conceptualization and tools have inherent inadequacies [ 69 , 76 , 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…As has been shown previously, the level of responsiveness especially in communication and autonomy dimensions perceived higher by patients in Iranian private clinics than in public ones (29). Therefore, it might conclude that communication and patient-centered have gotten a lot of attention in private clinics in service previous study showed that Iranian physicians could have a determining contribution to a patient's choice of a hospital.…”
Section: Communication Preferencementioning
confidence: 60%